A brief review on the synthesis, characterisation and analytical applications of nitrogen doped carbon dots. Issue 9 (17th February 2022) - Naik, Vaibhav M.; Bhosale, Sheshanath V.; Kolekar, Govind B.
Abstract : The analytical applications of NCDs as an optical sensor for sensing broad range species such as various cations and anions, molecules, and biologically important species, and gases, pH and temperature. Abstract : Since their discovery in 2004, fluorescent carbon nanoparticles have been tremendously studied due to their tunable optical properties. Recent studies on the synthesis and application of doped carbon dots highlight the effortless doping strategy with high quantum yields and applications in diverse fields. Among these, nitrogen doped carbon dots (NCDs) have been extensively investigated for their potential analytical and biological applications. This review features the synthetic methods and important characterisation studies required to verify successful synthesis of nitrogen doped carbon dots. Analytical applications of NCDs in metal ion, biomolecule, temperature, pH and gas sensing along with cell imaging and drug delivery applications are also discussed.